Satellite observation of chlorophyll and nutrients increase induced by Typhoon Megi in the Japan/East Sea - Son, S; Platt, T; Bouman, H; Lee, D; Sathyendranath, S (2006)
Remotely-sensed sea surface temperature (SST) and chlorophyll data were used to assess the biological response to the Typhoon Megi in the Japan/ East Sea (JES). Mean SST from in situ measurements and satellite data decreased by about 2-4°C in the JES after Typhoon Megi. Mean concentration of MODIS chlorophyll in the post-typhoon period increased by about 70% along the typhoon passage. The cold, nutrient-rich waters entrained into the surface layer lead to an enhancement of phytoplankton growth. Typhoon-induced variability of nitrate, phosphate, and silicate at the sea surface of the JES were derived from the MODIS SST using a nutrient-temperature relationship based on in situ measurements. After the passage of the typhoon, there were increases in NO3, PO4, and SiO2 by about 90%, 40%, and 35%, respectively. The nutrient flux brought into the surface water by the storm-induced mixing has the potential to support new production. Copyright 2006 by the American Geophysical Union.